Anode active material, anode including the same, secondary battery including the same, and method for producing anode active material
Patent Information
- Application Number
- JP2024548640
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-18
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2043-09-11
AI Technical Summary
【0015】
本発明の一実施態様による負極活物質は、SiOx(0
Smart Images

Figure 2025506711000001 
Figure 2025506711000002 
Figure 2025506711000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode active material, a negative electrode including the same, a secondary battery including the same, and a method for producing the negative electrode active material.
[0002] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0134148, filed with the Korean Intellectual Property Office on October 18, 2022, the entire contents of which are incorporated herein by reference. [Background technology]
[0003] Recently, with the rapid spread of electronic devices using batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for secondary batteries that are small, lightweight, and have a relatively high capacity is rapidly increasing. In particular, lithium secondary batteries are in the spotlight as a driving power source for portable devices because of their light weight and high energy density. As a result, research and development efforts to improve the performance of lithium secondary batteries are being actively carried out.
[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, an electrolyte, and an organic solvent. In addition, the positive electrode and the negative electrode may have active material layers formed on current collectors, each of which includes a positive electrode active material and a negative electrode active material. In general, the positive electrode uses a lithium-containing metal oxide such as LiCoO2 or LiMn2O4 as a positive electrode active material, and the negative electrode uses a lithium-free carbon-based active material or a silicon-based active material as a negative electrode active material.
[0005] Silicon-based negative active materials have been attracting attention because they have higher capacity and excellent high-speed charging characteristics compared to carbon-based active materials. However, silicon-based active materials have the disadvantage of low initial efficiency due to large volume expansion / contraction during charging / discharging and large irreversible capacity.
[0006] On the one hand, in the case of silicon-based active materials, specifically silicon-based oxides represented by SiOx (0 < x < 2), there is an advantage in that the degree of volume expansion / shrinkage due to charge / discharge is lower compared to other silicon-based active materials such as silicon (Si). However, there is still a disadvantage in that the initial efficiency of silicon-based oxides is reduced due to the presence of irreversible capacity.
[0007] Regarding this, research has been continuously conducted to reduce the irreversible capacity and improve the initial efficiency by doping or inserting metals such as Li, Al, and Mg into silicon-based oxides. However, in the case of a negative electrode slurry containing a metal-doped silicon-based oxide as a negative electrode active material, there is a problem that the metal oxide formed by doping reacts with moisture to increase the pH of the negative electrode slurry and change the viscosity, resulting in a poor state of the manufactured negative electrode and a decrease in the charge / discharge efficiency of the negative electrode.
[0008] Therefore, there is a need to develop a negative electrode active material that can improve the phase stability of a negative electrode slurry containing a silicon-based oxide and improve the charge / discharge efficiency of the negative electrode manufactured therefrom.
Prior Art Documents
Patent Documents
[0009]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0010] The present invention relates to a negative electrode active material, a negative electrode containing the same, a secondary battery containing the same, and a method for manufacturing the negative electrode active material.
Means for Solving the Problems
[0011] One embodiment of the present invention is SiO xSilicon-based particles containing (0 < x < 2) and a Li compound; a first carbon layer provided on at least a part of the surface of the silicon-based particles; a second carbon layer provided on at least a part of the surface of the first carbon layer; LiF; and CF a (0 < a < 4) is provided to provide a negative electrode active material.
[0012] One embodiment of the present invention provides a negative electrode including the negative electrode active material.
[0013] One embodiment of the present invention provides a secondary battery including the negative electrode.
[0014] One embodiment of the present invention is SiO x Forming silicon-based particles containing (0 < x < 2) and a Li compound and having a first carbon layer provided on at least a part of the surface; causing a second carbon layer to be provided on at least a part of the surface of the first carbon layer; and subjecting the silicon-based particles to fluorine plasma treatment; A method for manufacturing the negative electrode active material is provided, including these steps.
Effects of the Invention
[0015] The negative electrode active material according to one embodiment of the present invention is SiO x Silicon-based particles containing (0 < x < 2) and a Li compound; a first carbon layer provided on at least a part of the surface of the silicon-based particles; a second carbon layer provided on at least a part of the surface of the first carbon layer; LiF; and CF a (0 < a < 4), and when the negative electrode active material is used, it has the effect of improving the water-based processability of the slurry. Specifically, LiF is poorly soluble in water and can efficiently passivate silicon-based particles in an aqueous slurry, acting as an artificial SEI layer during battery operation and improving the life performance of the battery. CF a(0 < a < 4) can increase the hydrophobicity of the carbon layer, suppress the reaction between water and the negative electrode active material in the aqueous slurry, and can effectively passivate the particles. Further, the negative electrode active material includes two layers of carbon layers, and can maximize the hydrophobicity of the carbon layer during fluorine plasma treatment, thereby improving the particle passivation effect.
[0016] Therefore, the negative electrode including the negative electrode active material according to an embodiment of the present invention and the secondary battery including the negative electrode have the effect of improving the discharge capacity, initial efficiency, resistance performance, and / or life characteristics of the battery.
Embodiments for Carrying Out the Invention
[0017] Hereinafter, the present specification will be described in more detail.
[0018] In the present specification, when a certain part "includes" a certain component, this means that, unless otherwise stated, it does not exclude other components, but may further include other components.
[0019] In the present specification, when a certain member is located "on" another member, this includes not only the case where a certain member is in contact with another member, but also the case where there is another member between the two members.
[0020] The terms and words used in the present specification should not be construed as being limited to their ordinary or dictionary meanings. The inventors should interpret them in accordance with the meaning and concept consistent with the technical idea of the present invention in accordance with the principle that they can appropriately define the concept of the terms in order to explain their invention in the best way.
[0021] The singular expressions of the terms used in the present specification include plural expressions unless the context clearly indicates otherwise.
[0022] In this specification, the crystallinity of the structure contained in the negative electrode active material can be confirmed by X-ray diffraction analysis. The X-ray diffraction analysis may be performed using an X-ray diffraction (XRD) analyzer (product name: D4-endavor, manufacturer: bruker), and in addition to the said device, devices used in the art may also be appropriately adopted.
[0023] In this specification, the presence and content of elements in the negative electrode active material can be confirmed by ICP analysis. The ICP analysis can be performed using an inductively coupled plasma optical emission spectrometer (ICPAES, Perkin-Elmer 7300).
[0024] In this specification, the average particle size (D 50 ) can be defined as the particle size at the 50% volume cumulative amount reference in the particle size distribution curve (graph curve of the particle size distribution diagram). The average particle size (D 50 ) can be measured, for example, using the laser diffraction method. The laser diffraction method can generally measure particle sizes ranging from the submicron region to about several millimeters, and results with high reproducibility and high resolution can be obtained.
[0025] Hereinafter, preferred embodiments of the present invention will be described in detail. However, the embodiments of the present invention may be deformed into various forms, and the scope of the present invention is not limited to the embodiments described below.
[0026] <Negative electrode active material> One embodiment of the present invention is a silicon-based particle containing SiO x (0 < x < 2) and a Li compound; a first carbon layer provided on at least a part of the surface of the silicon-based particle; a second carbon layer provided on at least a part of the surface of the first carbon layer; LiF; and CF a (0 < a < 4), providing a negative electrode active material.
[0027] The negative electrode active material according to one embodiment of the present invention contains silicon-based particles. The silicon-based particles are SiO xIt contains SiO(0 < x < 2) and a Li compound.
[0028] The SiO x (0 < x < 2) may correspond to a matrix within the silicon-based particles. The SiO x (0 < x < 2) may be in a form containing Si and / or SiO2, and the Si may form a phase. That is, the x corresponds to the number ratio of O to Si contained in the SiO x (0 < x < 2). When the silicon-based particles contain the SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved.
[0029] The Li compound may correspond to a matrix within the silicon-based composite particles. The Li compound may exist in at least one form of lithium atoms, lithium silicate, silicide, and lithium oxide within the silicon-based particles. When the silicon-based particles contain a Li compound, it has the effect of improving the initial efficiency.
[0030] The Li compound can be distributed on the surface and / or inside of the silicon-based particles in a form doped into the silicon-based particles. The Li compound is distributed on the surface and / or inside of the silicon-based particles, can control the volume expansion / contraction of the silicon-based particles to an appropriate level, and can play a role in preventing damage to the active material. Also, the Li compound can be contained in terms of reducing the ratio of the irreversible phase (e.g., SiO2) of the silicon-based oxide particles and increasing the efficiency of the active material.
[0031] In one embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is Li a Si b O c(2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be divided into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate may exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-based particles, and the amorphous lithium silicate is Li a Si b O c It may have a complex structure of the form (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.
[0032] In one embodiment of the present invention, based on 100 parts by weight of the entire negative electrode active material, Li may be contained in an amount of 0.1 part by weight to 40 parts by weight or 0.1 part by weight to 25 parts by weight. Specifically, it may be contained in an amount of 1 part by weight to 25 parts by weight, and more specifically, it may be contained in an amount of 2 parts by weight to 20 parts by weight. As the content of Li increases, the initial efficiency increases, but there is a problem that the discharge capacity decreases. Therefore, when the above range is satisfied, appropriate discharge capacity and initial efficiency can be realized.
[0033] The content of the Li element can be confirmed by ICP analysis. Specifically, after collecting a certain amount (about 0.01 g) of the negative electrode active material, it is transferred to a platinum crucible, nitric acid, hydrofluoric acid, and sulfuric acid are added, and it is completely decomposed on a hot plate. Then, using an inductively coupled plasma atomic emission spectrometer (ICPAES, Perkin-Elmer 7300), at the characteristic wavelength of the element to be analyzed, the intensity of the standard solution prepared using a standard solution (5 mg / kg) is measured to create a standard calibration curve. Then, the pretreated sample solution and the blank sample are introduced into the instrument, the intensities of each are measured to calculate the actual intensity, and after calculating the concentration of each component by comparing with the created calibration curve, it is converted so that the sum of the whole becomes the theoretical value, and the element content of the manufactured negative electrode active material can be analyzed.
[0034] In one embodiment of the present invention, the silicon-based particles may include additional metal atoms. The metal atoms may be present in the silicon-based particles in at least one form of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may include at least one selected from the group consisting of Mg, Li, Al, and Ca. This can improve the initial efficiency of the negative electrode active material.
[0035] In one embodiment of the present invention, the silicon-based particles have a first carbon layer on at least a part of the surface. In this case, the first carbon layer may be in a form that partially covers at least a part of the surface, i.e., the particle surface, or the entire particle surface. The first carbon layer imparts electrical conductivity to the negative electrode active material, and the initial efficiency, life characteristics, and battery capacity characteristics of the secondary battery can be improved.
[0036] In one embodiment of the present invention, a second carbon layer may be provided on at least a portion of the surface of the first carbon layer. When two carbon layers are provided as described above, the particles can be passivated more easily to effectively prevent the reaction of the silicon-based particles or lithium by-products with water, and the hydrophobicity of the carbon layer can be maximized during fluorine plasma treatment to improve passivation characteristics.
[0037] In one embodiment of the invention, the first and second carbon layers comprise amorphous carbon.
[0038] The first and second carbon layers may further include crystalline carbon.
[0039] The crystalline carbon can further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.
[0040] The amorphous carbon can appropriately maintain the strength of the carbon layer and suppress the expansion of the silicon-based particles. The amorphous carbon may be a carbon-based material formed by using at least one carbide or hydrocarbon selected from the group consisting of tar, pitch, and other organic substances as a source of a chemical vapor deposition method.
[0041] The carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose, or ketohexose, and combinations thereof.
[0042] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, or hexane. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, or phenanthrene.
[0043] In one embodiment of the present invention, the first and second carbon layers may be amorphous carbon layers.
[0044] In one embodiment of the present invention, the total content of the first carbon layer and the second carbon layer may be 1 to 50 parts by weight, 1 to 30 parts by weight, or 1 to 20 parts by weight based on 100 parts by weight of the total negative active material. More specifically, it may be 1 to 15 parts by weight, 2 to 10 parts by weight, 3 to 7 parts by weight, or 4 to 6 parts by weight. When the content is within the above range, it is possible to prevent a decrease in capacity and efficiency of the negative active material.
[0045] In one embodiment of the present invention, the first carbon layer may be included in an amount of 0.5 to 5 parts by weight, 1 to 5 parts by weight, 2 to 5 parts by weight, 2 to 4.5 parts by weight, or 2 to 4 parts by weight based on 100 parts by weight of the entire negative electrode active material. More specifically, it may be included in an amount of 3 to 4 parts by weight. When the above range is satisfied, it is possible to prevent a decrease in the capacity and efficiency of the negative electrode active material.
[0046] In one embodiment of the present invention, the second carbon layer may be included in an amount of 0.5 to 5 parts by weight, 1 to 5 parts by weight, specifically 1.5 to 3 parts by weight, and more specifically 2 to 3 parts by weight based on 100 parts by weight of the entire negative electrode active material. When the above range is satisfied, it is possible to prevent a decrease in the capacity and efficiency of the negative electrode active material, and effectively passivate the negative electrode active material.
[0047] In one embodiment of the present invention, the thicknesses of the first carbon layer and the second carbon layer may each be 1 nm to 500 nm, specifically 5 nm to 300 nm. When the above range is satisfied, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, the side reaction between the electrolyte and the negative electrode active material is suppressed, and the initial efficiency and / or life of the battery is improved.
[0048] Specifically, the carbon layer can be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.
[0049] In one embodiment of the present invention, the negative electrode active material may include LiF; and CF a (0 < a < 4).
[0050] Specifically, during the production of the negative electrode active material, at least a part of the surface of the silicon-based particles is provided with a first carbon layer, and after a second carbon layer is provided on at least a part of the surface of the first carbon layer, F can be introduced through fluorine plasma treatment on the surface of the silicon-based particles provided with the two carbon layers. In this process, F can be introduced into the lithium by-products generated when the silicon-based particles are doped with Li to form LiF, and F can be introduced into the carbon of the carbon layer provided on the surface of the silicon-based particles to form CF a It may exist in the form of (0 < a < 4).
[0051] The LiF formed as described above is not easily soluble in water, can efficiently passivate the silicon-based particles with an aqueous slurry, prevent the elution of the Li compound contained in the silicon-based particles, prevent the slurry from becoming basic, and has the effect of improving the aqueous processability. In addition, LiF acts as an artificial SEI film during the operation of the battery, and has the effect of improving the life performance of the battery.
[0052] In one embodiment of the present invention, the LiF and CF a (0 < a < 4) may be provided on the silicon-based particles.
[0053] In one embodiment of the present invention, the LiF and CF a (0 < a < 4) may be provided on the outermost surface of the negative electrode active material.
[0054] The LiF may be provided on the surface of the silicon-based particles, inside the first carbon layer, on the surface of the first carbon layer, inside the second carbon layer, or on the surface of the second carbon layer. Specifically, the LiF may be provided on at least a part of the first carbon layer or the second carbon layer, or on at least a part of the region of the surface of the silicon-based particles where the first carbon layer or the second carbon layer is not provided. It is not limited thereto, and the LiF may be formed at a position where lithium by-products or lithium silicate exist in the negative electrode active material.
[0055] The LiF may partially cover the surface or may cover the entire surface. Examples of the shape of the LiF include an island type or a thin film type, but the shape of the LiF is not limited thereto.
[0056] Alternatively, the LiF may be provided on the surface of the silicon-based particles by introducing F into the Li compound contained in the silicon-based particles.
[0057] The CF a (0 < a < 4) may be provided inside the first carbon layer, on the surface of the first carbon layer, inside the second carbon layer, or on the surface of the second carbon layer.
[0058] Specifically, the CF a (0 < a < 4) is formed by introducing F onto the surface of the first carbon layer or the second carbon layer and has a structure containing a C-F bond. That is, the CF a (0 < a < 4) may be located inside the first carbon layer or the second carbon layer or may be located on the surface of the first carbon layer or the second carbon layer. Specifically, it may be mainly located near the surface of the second carbon layer.
[0059] By introducing F onto the surface of the first carbon layer or the second carbon layer to form CF a (0 < a < 4), the hydrophobicity of the entire carbon layer increases, and the reaction between moisture and the negative electrode active material in the aqueous slurry is suppressed, so that the particles can be effectively passivated.
[0060] In one embodiment of the present invention, the negative electrode active material may further contain SiF b (0 < b < 4). When F is introduced onto the surface of the silicon-based particles by fluorine plasma treatment, F may also be introduced into the silicon-based particles, and Si-F bonds are formed with silicon inside the particles, and SiF b (0 < b < 4) may exist in the form. The SiF b(0 < b < 4) may be located inside the silicon-based particles or on the surface of the silicon-based particles. Specifically, it may be mainly located near the surface of the silicon-based particles.
[0061] The components contained in the negative electrode active material can be confirmed by X-ray diffraction analysis (XRD) or X-ray photoelectron spectroscopy (XPS).
[0062] In the present invention, the element content and atomic ratio on the surface of the negative electrode active material can be confirmed by XPS (Nexsa ESCA System, Thermo Fisher Scientific (ESCA-02)).
[0063] Specifically, for each sample, after obtaining a survey scan spectrum and a narrow scan spectrum, a survey scan spectrum and a narrow scan spectrum can be obtained while performing a depth profile. The depth profile can be performed up to 3000 seconds using monatomic Ar ions, and the measurement and data processing conditions are as follows.
[0064] - X-ray source: Monochromated Al Kα (1486.6 eV) - X-ray spot size: 400 μm - Sputtering gun: Monatomic Ar (energy: 1000 eV, current: low, raster width: 2 mm) - Etching rate: 0.09 nm / s for Ta2O5 - Operation Mode: CAE (Constant Analyzer Energy) mode -Survey scan: pass energy 200eV, energy step 1eV -Narrow scan: scanned mode, pass energy 50eV, energy step 0.1eV -Charge compensation: flood gun off -SF:Al THERMO1 -ECF:TPP-2M -BG subtraction: Shirley
[0065] In one embodiment of the present invention, the X-ray photoelectron spectroscopy (XPS) depth profile can be measured under a Monochromated Al K α X-ray source at 0.09 nm / s for up to 3000 seconds.
[0066] In one embodiment of the present invention, Li, Si, C, N, O or F is detected when the negative electrode active material is analyzed by X-ray photoelectron spectroscopy.
[0067] Hereinafter, the elemental content by X-ray photoelectron spectroscopy is based on 100 at% of the sum of all elements measured on a 100s basis.
[0068] In one embodiment of the present invention, the F content according to surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 10 at % or more, and the Li content may be less than 10 at %.
[0069] Specifically, the F content may be 10 at% to 50 at%, 15 at% to 40 at%, 20 at% to 40 at%, 25 at% to 35 at%, or 20 at% to 30 at%. The lower limit of the F content may be 10 at%, 15 at%, 20 at%, 22 at%, 24 at%, or 25 at%, and the upper limit may be 50 at%, 45 at%, 40 at%, 35 at%, 33 at%, or 30 at%.
[0070] When the F element content on the surface of the negative active material satisfies the above range, F can be sufficiently introduced into the negative active material to remove lithium by-products, and F can be effectively introduced into the carbon layer, thereby preventing the negative active material from reacting with water in an aqueous slurry or preventing lithium by-products from being eluted, thereby improving aqueous processability.
[0071] When the F content is equal to or greater than the lower limit of the range, the amount of F introduced into the surface of the negative active material is appropriate, and a passivation effect is exhibited. When the F content is equal to or less than the upper limit of the range, the generation of a large number of unstable F bonds such as C—F and Si-F can be prevented, and the generation of HF in the aqueous slurry and the decomposition of components such as CMC due to HF can be suppressed, thereby preventing a decrease in viscosity.
[0072] In one embodiment of the present invention, the Li content according to the surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be less than 10 at%. Specifically, the Li content may be 0.1 at% or more and less than 10 at%, 0.5 at% or more and less than 7 at%, 1 at% or more and less than 5 at%, 1 at% or more and less than 3 at%, or 1.5 at% or more and less than 2.5 at%. The lower limit of the Li content may be 0.1 at%, 0.5 at%, 1 at%, 1.5 at%, or 2 at%, and the upper limit may be 9.9 at%, 7 at%, 5 at%, 4 at%, 3 at%, or 2.5 at%.
[0073] When the Li element content on the surface of the negative active material satisfies the above range, the second carbon layer is uniformly formed, minimizing contact with water when applied to an aqueous process, thereby suppressing gas generation. When the Li content is above the lower limit of the range, the properly formed carbon layer acts as a resistor for lithium diffusion during battery operation to prevent deterioration of battery performance, and when the Li content is below the upper limit of the range, a uniform carbon layer is formed and a large amount of Li appears on the surface, suppressing gas generation in an aqueous process.
[0074] In one embodiment of the present invention, the Si content by surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 7 at% or less. Specifically, the Si content may be 0.1 at% to 7 at%, 0.5 at% to 5 at%, 1 at% to 4 at%, 1.5 at% to 3.5 at%, or 1.5 at% to 3 at%. The lower limit of the Si content may be 0.1 at%, 0.5 at%, 1 at%, or 1.5 at%, and the upper limit may be 7 at%, 5 at%, 4 at%, 3.5 at%, or 3 at%.
[0075] When the Si content on the surface of the negative active material satisfies the above range, a suitable and uniform carbon layer is formed and Si is not present, minimizing contact with water and improving aqueous processability. When the Si content is above the lower limit of the range, components other than Si present on the surface can be prevented from acting as resistors during battery operation, thereby preventing deterioration of battery performance, and when the Si content is below the upper limit of the range, gas generation due to contact between Si and water can be prevented.
[0076] In one embodiment of the present invention, the C content according to surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 50 at% or more. Specifically, the C content may be 50 at% or more and 80 at% or less, 55 at% or more and 75 at% or less, 55 at% or more and 70 at% or less, or 60 at% or more and 70 at% or less. The lower limit of the C content may be 50 at%, 55 at%, or 60 at%, and the upper limit may be 80 at%, 75 at%, or 70 at%.
[0077] When the C element satisfies the above content on the surface of the negative active material, a uniform carbon layer is formed, and gas generation is improved due to the passivation effect. When the C content is above the lower limit of the range, the uniformity increases and the possibility of contact with water is reduced, preventing gas generation in aqueous processes. When the C content is below the upper limit of the range, the appropriate amount of carbon layer can prevent a decrease in battery performance due to an excessive increase in resistance during battery operation and can prevent gas generation due to contact between Si and water.
[0078] In one embodiment of the present invention, the O content by surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 15 at% or less. Specifically, the O content may be 0.1 at% to 15 at%, 0.1 at% to 10 at%, 0.3 at% to 5 at%, 0.3 at% to 3 at%, or 0.5 at% to 2.5 at%. The lower limit of the O content may be 0.1 at%, 0.3 at%, 0.5 at%, 0.7 at%, or 0.8 at%, and the upper limit may be 15 at%, 10 at%, 5 at%, 3 at%, or 2.5 at%.
[0079] When the O element on the surface of the negative active material satisfies the above content, an appropriate amount of F is introduced to reduce O and increase the non-hydrophilicity of the surface, thereby blocking contact with water and maximizing the passivation effect, thereby suppressing gas generation in aqueous processes. When the O content is above the lower limit of the range, HF generation due to the bond of unstable F element can be suppressed, thereby suppressing the decomposition reaction of materials such as CMC in the slurry and preventing a sudden decrease in viscosity. When the O content is below the upper limit of the range, hydrophilicity is reduced and it does not easily react with water, preventing gas generation.
[0080] When the negative electrode active material of the present invention satisfies the above-mentioned element content range, F is sufficiently introduced into the negative electrode active material, lithium by-products are easily removed, and LiF is formed. F is effectively introduced into the carbon layer, and CF aThe resulting LiF and CF a The amount of the aqueous solution is appropriate, and thus it is possible to prevent the negative active material from reacting with water in the aqueous slurry or prevent lithium by-products from being eluted, thereby improving the aqueous processability.
[0081] In one embodiment of the present invention, the atomic ratio of F to O (F / O ratio) in surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may be 1 or more. Specifically, it may be 1 or more and 50 or less, 5 or more and 50 or less, or 10 or more and 40 or less. When the above range is satisfied, F is appropriately introduced into the surface portion of the negative electrode active material, and LiF and CF a is easily formed, silicon-based particles are easily passivated in the slurry, and LiF acts as an artificial SEI film during battery operation, resulting in significant improvements in slurry processability and life performance. When the amount of F introduced into the surface of the negative electrode active material is greater than the lower limit of the range, the amount of F introduced is sufficient, which is favorable for passivation effects, and when the amount of F introduced is less than the upper limit of the range, the generation of a large number of unstable F bonds such as CF and Si-F is prevented, and the generation of HF in the aqueous slurry and the decomposition of components such as CMC in the slurry due to HF are suppressed, thereby preventing a significant decrease in viscosity.
[0082] In one embodiment of the present invention, the atomic ratio of C to Li (C / Li ratio) in the surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy may exceed 10. Specifically, it may be 15 or more and 50 or less, 20 or more and 40 or less, or 25 or more and 35 or less. When the above range is satisfied, LiF and CF located on the surface portion of the negative electrode active material may be 10 or more. aThe content is appropriate and can easily passivate silicon-based particles in the slurry. When the battery is driven, LiF acts as an artificial SEI film, resulting in a remarkable improvement in the processability and life performance of the slurry. When it is above the lower limit of the above range, a carbon layer can be appropriately formed, and when the battery is driven, the decrease in battery performance caused by acting as a resistance body for lithium diffusion can be prevented. When it is below the upper limit of the above range, the uniformity of the carbon layer increases, and the generation of gas in the aqueous process due to the appearance of a large amount of Li on the surface can be prevented.
[0083] In one embodiment of the present invention, the negative electrode active material can satisfy the following formula A.
Number
[0084] In the formula A, the element content is based on the surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy and is based on the sum of all elements measured on a 100 s basis of 100 at%.
[0085] Specifically, the {(element content of F) × (element content of C)} / {(element content of Li) × (element content of Si) × (element content of O)} may be 50 or more, 80 or more, 100 or more, or 120 or more, and may be 1000 or less, 800 or less, 700 or less, or 600 or less.
[0086] When the above range is satisfied, the content of CF containing a C-F bond in the surface part of the negative electrode active material a (0 < a < 4) becomes high, the hydrophobicity of the carbon layer is maximized, and the passivation effect of the particles is excellent.
[0087] In one embodiment of the present invention, the CF a(0 < a < 4) may have a content greater than that of LiF. Usually, after forming the first carbon layer on the silicon-based particles, during the process of doping lithium into the silicon-based particles, the lithium by-products mainly exist on the first carbon layer. Then, after providing the second carbon layer on the first carbon layer, when the silicon-based particles are treated with fluorine plasma, F is preferentially introduced into the carbon layer, so CF a (0 < a < 4) may have a content greater than that of LiF. As described above, CF a When the content of (0 < a < 4) is greater than that of LiF, the hydrophobicity of the carbon layer is maximized, and the passivation effect of the particles is excellent.
[0088] In one embodiment of the present invention, lithium by-products may be present on the silicon-based particles. Specifically, the lithium by-products may be present on the surface of the silicon-based particles or on the surface of the carbon layer.
[0089] Specifically, the lithium by-products may mean lithium compounds remaining near the surface of the silicon-based particles or the carbon layer after manufacturing the silicon-based particles. As described above, even after the acid treatment step, there may be lithium by-products that were unreacted with the acid remaining.
[0090] The lithium by-products may include one or more selected from the group consisting of Li2O, LiOH, and Li2CO3. As in the above reaction, LiF is formed during the fluorine plasma treatment of the lithium by-products, and unreacted lithium by-products may be present on the silicon-based particles.
[0091] Whether the lithium by-products are present or not can be confirmed by X-ray diffraction analysis (XRD) or X-ray photoelectron spectroscopy (XPS).
[0092] The lithium by-product may be included in an amount of 5 parts by weight or less based on 100 parts by weight of the total negative electrode active material. Specifically, the lithium by-product may be included in an amount of 0.01 to 5 parts by weight, 0.05 to 2 parts by weight, or 0.1 to 1 part by weight. More specifically, the lithium by-product may be included in an amount of 0.1 to 0.8 parts by weight, or 0.1 to 0.5 parts by weight. When the content of the lithium by-product satisfies the above range, it is possible to reduce side reactions in the slurry and improve aqueous processability by reducing viscosity changes. When the content is below the upper limit of the above range, it is possible to prevent the slurry from becoming alkaline during formation, and to minimize the occurrence of problems in aqueous processability due to side reactions or viscosity changes.
[0093] The content of the lithium by-product may be calculated by measuring the amount of the HCl solution at a specific range where the pH changes during the titration of the aqueous solution including the negative active material with the HCl solution using a titration device.
[0094] The average particle size (D 50 ) may be 0.1 μm to 30 μm, specifically 1 μm to 20 μm, and more specifically 1 μm to 10 μm. When the above range is satisfied, the structure of the active material during charging and discharging is stabilized, the problem of the particle size becoming too large and the volume expansion / contraction level becoming too large, and the problem of the particle size becoming too small and the initial efficiency decreasing can be prevented.
[0095] The BET specific surface area of the negative electrode active material is 1 m 2 / g~100m 2 / g, specifically, 1m 2 / g~70m 2 / g, more specifically, 1m 2 / g~50m 2 / g, e.g., 2m 2 / g~30m 2 When the content of the electrolyte is within this range, side reactions with the electrolyte may be reduced during charging and discharging of the battery, and the life characteristics of the battery may be improved.
[0096] <Method for manufacturing negative electrode active material> One embodiment of the present invention forms silicon-based particles containing SiO x (0 < x < 2) and a Li compound, and having a first carbon layer on at least a part of the surface; forming a second carbon layer on at least a part of the surface of the first carbon layer; and subjecting the silicon-based particles to fluorine plasma treatment; The method for manufacturing the negative electrode active material is provided.
[0097] The silicon-based particles can be formed by heating and vaporizing Si powder and SiO2 powder in a vacuum, then depositing the vaporized mixed gas to form preliminary particles; forming a carbon layer on the surface of the formed preliminary particles; and after mixing the preliminary particles with the carbon layer formed and Li powder, performing heat treatment.
[0098] Specifically, the mixed powder of the Si powder and the SiO2 powder can be heat-treated at 1300°C to 1800°C, 1400°C to 1800°C, or 1400°C to 1600°C under vacuum.
[0099] The formed preliminary particles may have the form of SiO.
[0100] The first carbon layer can be formed by using chemical vapor deposition (CVD) with a hydrocarbon gas or by a method of carbonizing a substance serving as a carbon source.
[0101] Specifically, after the formed preliminary particles are put into a reactor, they can be formed by chemical vapor deposition (CVD) of a hydrocarbon gas at 600°C to 1200°C. The hydrocarbon gas may be at least one hydrocarbon gas selected from the group including methane, ethane, propane, and acetylene, and can be heat-treated at 900°C to 1000°C.
[0102] The step of heat-treating after mixing the preliminary particles with the first carbon layer formed and Li powder may be carried out at 700 °C to 900 °C for 4 hours to 6 hours. Specifically, it may be carried out at 800 °C for 5 hours.
[0103] The silicon-based particles may contain, as the Li compound, Li silicate, Li silicide, Li oxide, or the like.
[0104] The particle size of the silicon-based particles can be adjusted by methods such as a ball mill, a jet mill, or air classification, but is not limited thereto.
[0105] As described above, at least a part of the surface of the silicon-based particles provided with the first carbon layer is provided with a lithium compound (lithium by-product). Specifically, in the process of forming preliminary particles containing SiO x (0 < x < 2), forming the first carbon layer on the preliminary particles, and then doping with Li to produce the silicon-based particles, a lithium compound, that is, a lithium by-product formed by unreacted lithium, remains near the surface of the silicon-based particles.
[0106] In one embodiment of the present invention, the method for manufacturing the negative electrode active material includes a step of providing a second carbon layer on at least a part of the surface of the first carbon layer.
[0107] The second carbon layer can be formed by using chemical vapor deposition (CVD) using a hydrocarbon gas or a method of carbonizing a substance serving as a carbon source.
[0108] Specifically, the preliminary particles having the first carbon layer are put into a reactor, and then a hydrocarbon gas is subjected to chemical vapor deposition (CVD) at less than 800° C. The hydrocarbon gas may be at least one type of hydrocarbon gas selected from the group including methane, ethane, propane, and acetylene, and the heat treatment may be performed at 600 to less than 800° C. for 2 to 4 hours. For example, the heat treatment may be performed under conditions of 700° C. for 3 hours in an acetylene or propane gas atmosphere.
[0109] As described above, the second carbon layer can be formed with an increased degree of amorphization by performing heat treatment at a temperature of less than 800°C. By increasing the degree of amorphization of the second carbon layer, the residual lithium by-products can be effectively covered, which has the effect of minimizing side reactions with moisture and improving fast charging performance. On the other hand, when the degree of amorphization of the second carbon layer is low, i.e., when the degree of crystallinity is high, carbon coating is performed at a relatively high temperature, which increases the crystal grain size of Si, thereby deteriorating the life performance.
[0110] By forming the carbon layer in two layers as described above, it is possible to suppress side reactions caused by unreacted lithium compounds, and to maximize the hydrophobicity of the carbon layer when fluorine is introduced in a fluorine plasma process described below.
[0111] In one embodiment of the present invention, the method for producing the negative electrode active material includes subjecting the silicon-based particles to a fluorine plasma treatment.
[0112] The fluorine plasma treatment step includes the steps of: introducing the silicon-based particles into a plasma chamber, followed by injecting CF4 gas; increasing the pressure within the chamber; and forming a plasma in the chamber.
[0113] The plasma treatment may be performed using RF plasma.
[0114] Specifically, the pressure in the chamber before injecting CF4 gas into the chamber may be adjusted to 0.01 torr to 0.1 torr. Preferably, the pressure may be adjusted to 0.05 torr to 0.09 torr or 0.07 torr.
[0115] Thereafter, in the step of increasing the pressure inside the chamber, the pressure inside the chamber may be adjusted to 0.1 torr to 0.5 torr. Specifically, the pressure may be adjusted to 0.15 torr to 0.3 torr or 0.2 torr.
[0116] The step of forming plasma in the chamber may be performed by applying power to the chamber, and more specifically, the power may be 50W to 300W, 80W to 250W, or 100W to 200W.
[0117] The plasma may be maintained for 1 to 10 minutes, preferably 3 to 8 minutes, 5 to 7 minutes, or 6 minutes.
[0118] When the plasma treatment is performed while satisfying the above range, F can be introduced into the negative electrode active material in an appropriate content.
[0119] Plasma can be formed in the chamber to introduce F into the negative electrode active material, and then the vacuum can be released at normal pressure and the sample can be collected.
[0120] The fluorine plasma treatment step may be repeated two or more times, and preferably, it may be performed twice.
[0121] When F is introduced into the negative active material by a dry method using plasma as in the present invention, lithium inside the silicon-based particles containing Li compounds does not melt, and the passivation properties are further improved. On the other hand, when F is introduced by a method such as hydrothermal synthesis or solvothermal synthesis, the surface of the silicon-based particles becomes porous, and the passivation effect is reduced.
[0122] As described above, when doping silicon-based particles with lithium by fluorine plasma treatment, F is introduced into the lithium by-products formed, and LiF is formed. The formed LiF can easily block the reaction between water and lithium compounds or silicon-based particles, and act as an artificial SEI layer during battery operation, resulting in improved life performance.
[0123] Also, when F is introduced onto the surface of the carbon layer to form CF a (0 < a < 4), the hydrophobicity of the carbon layer increases, suppressing the reaction between moisture and the negative electrode active material in the aqueous slurry, so that the particles can be effectively passivated.
[0124] <Negative electrode> The negative electrode according to an embodiment of the present invention may include the above-mentioned negative electrode active material.
[0125] Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Further, the negative electrode active material layer may further include a binder, a thickener, and / or a conductive material.
[0126] The negative electrode active material layer can be formed by applying a negative electrode slurry containing a negative electrode active material, a binder, a thickener, and / or a conductive material to at least one surface of the current collector, followed by drying and rolling.
[0127] The negative electrode slurry may further include an additional negative electrode active material.
[0128] The additional negative electrode active material may be a compound capable of reversibly inserting and extracting lithium. Specific examples of the additional negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, the carbon material may be either low-crystalline carbon or high-crystalline carbon. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, mesocarbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.
[0129] The additional anode active material may be a carbon-based anode active material.
[0130] In one embodiment of the present invention, the weight ratio of the negative electrode active material to the additional negative electrode active material contained in the negative electrode slurry may be 10:90 to 90:10, specifically, 10:90 to 50:50.
[0131] The negative electrode slurry may include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0132] The negative electrode slurry including the negative electrode active material according to one embodiment of the present invention may have a pH of 7 to 11 at 25° C. When the pH of the negative electrode slurry satisfies the above range, the rheological properties of the slurry are stabilized. On the other hand, when the pH of the negative electrode slurry is less than 7 or exceeds 11, decomposition of carboxymethyl cellulose (CMC) used as a thickener occurs, causing a decrease in the viscosity of the slurry, and thus causing a problem in that the degree of dispersion of the active material contained in the slurry is reduced.
[0133] The negative electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, or the like. Specifically, a transition metal that easily adsorbs carbon, such as copper or nickel, may be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but is not limited thereto.
[0134] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0135] The conductive material is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and examples of the conductive material that can be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0136] The conductive material may be contained in an amount of 0.01% by weight to 30% by weight, and preferably 0.1% by weight to 20% by weight, based on 100% by weight of the negative electrode active material layer.
[0137] The thickener may be carboxymethyl cellulose (CMC), but is not limited thereto, and any thickener used in the art may be appropriately adopted.
[0138] In one embodiment of the present invention, the weight ratio of the negative electrode active material and the additional negative electrode active material contained in the negative electrode slurry may be 1:99 to 30:70, specifically, 5:95 to 30:70 or 10:90 to 20:80.
[0139] In an embodiment of the present invention, the total amount of the negative electrode active material contained in the negative electrode slurry may be 60 parts by weight to 99 parts by weight, specifically, 70 parts by weight to 98 parts by weight, based on 100 parts by weight of a total solid content of the negative electrode slurry.
[0140] In one embodiment of the present invention, the binder may be included in an amount of 0.5 to 30 parts by weight, specifically 1 to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0141] In one embodiment of the present invention, the conductive material may be included in an amount of 0.5 to 25 parts by weight, specifically 1 to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0142] In one embodiment of the present invention, the thickener may be included in an amount of 0.5 parts by weight to 25 parts by weight, specifically, 0.5 parts by weight to 20 parts by weight, more specifically, 1 part by weight to 20 parts by weight, based on 100 parts by weight of the total solid content of the negative electrode slurry.
[0143] The negative electrode slurry according to an embodiment of the present invention may further include a solvent for forming the negative electrode slurry. Specifically, the solvent for forming the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of components.
[0144] In one embodiment of the present invention, the weight of the solid content of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on 100 parts by weight of the total of the negative electrode slurry.
[0145] <Secondary battery> A secondary battery according to an embodiment of the present invention may include the anode according to the embodiment described above. Specifically, the secondary battery may include an anode, a cathode, a separator interposed between the cathode and the anode, and an electrolyte, and the anode is the same as the anode described above. The anode has been described above, so a detailed description thereof will be omitted.
[0146] The positive electrode may include a positive electrode current collector, and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0147] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0148] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0149] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0150] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and other carbon-containing substances; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one of these may be used alone or a mixture of two or more of them may be used.
[0151] In addition, the positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector.Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.
[0152] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is normally used as a separator in a secondary battery can be used without any particular restrictions, and it is particularly preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte moisture absorption ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single layer or multilayer structure.
[0153] Examples of the electrolytic solution include, but are not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries.
[0154] Specifically, the electrolytic solution may contain a non-aqueous organic solvent and a metal salt.
[0155] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0156] In particular, among the carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, can be preferably used as high-viscosity organic solvents, because they have a high dielectric constant and dissociate lithium salts well. When such cyclic carbonates are mixed in an appropriate ratio with linear carbonates having low viscosity and low dielectric constant, such as dimethyl carbonate and diethyl carbonate, an electrolyte solution having high conductivity can be prepared, and therefore such a mixture can be used even more preferably.
[0157] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2- , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.
[0158] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0159] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0160] <Examples and Comparative Examples> Example 1 94g of powder of Si and SiO2 mixed in a 1:1 molar ratio was mixed in a reactor and then vacuum heated at 1400℃ sublimation temperature. The vaporized Si and SiO2 mixed gas was then reacted in a vacuum cooling zone with a cooling temperature of 800℃ to condense into a solid phase. The condensed particles were then crushed in a ball mill for 3 hours to produce particles with a size of 6μm. The particles were then placed in the hot zone of a CVD device while Ar gas was flowed to maintain an inert atmosphere, and the methane was blown into the hot zone at 900℃ using Ar as a carrier gas, and the mixture was heated for 5 hours and 10 minutes. -1 A carbon layer was formed on the surface of the particles by reacting at torr. Then, 6 g of Li metal powder was added and mixed with the particles with the carbon layer, and an additional heat treatment was performed at a temperature of 800°C in an inert atmosphere to produce silicon-based particles containing a Li compound.
[0161] The silicon-based particles are placed in a reactor, and acetylene is blown into a hot zone at 700° C. using Ar as a carrier gas. -1 The reaction was carried out at torr for 3 hours to produce silicon-based particles having a second carbon layer formed on the surface of the silicon-based particles.
[0162] 10 g of the silicon-based particles on which the second carbon layer was formed were thinly spread to a thickness of 3 mm or less and placed in an RF plasma chamber, and CF4 gas was injected under 0.07 torr to increase the pressure inside the chamber to 0.2 torr. Then, 150 W of power was applied to the chamber to generate plasma, and the chamber was held for 6 minutes, and the vacuum was released to normal pressure, and the sample was collected. The above process was repeated two more times (total of three times) to obtain the negative electrode active material of Example 1.
[0163] Example 2 A negative electrode active material of Example 2 was obtained in the same manner as in Example 1, except that the power intensity during plasma generation was 200 W.
[0164] Example 3 A negative electrode active material of Example 3 was obtained in the same manner as in Example 1, except that the power intensity during plasma generation was 100 W.
[0165] Comparative Example 1 A negative electrode active material of Comparative Example 1 was obtained in the same manner as in Example 1, except that the second carbon layer was not formed and the plasma treatment was not performed.
[0166] Comparative Example 2 A negative electrode active material of Comparative Example 2 was obtained in the same manner as in Example 1, except that the plasma treatment was not performed after the second carbon layer was formed.
[0167] Comparative Example 3 Silicon-based particles having a second carbon layer formed thereon were obtained in the same manner as in Example 1, except that no plasma treatment was performed.
[0168] The silicon-based particles and 0.1M HF solution were mixed in a weight ratio of 1:7, and then stirred for 1 hour. The mixture was then filtered, dried, and heat-treated at 300° C. to produce a negative electrode active material having a LiF layer on the surface.
[0169] <Carbon layer content measurement> The content of the carbon layer was analyzed using a CS-analyzer (CS-800, Eltra).
[0170] <Measurement of Li content in negative electrode active material> The Li atom content was confirmed by ICP analysis using an inductively coupled plasma optical emission spectrometer (Perkin-Elmer 7300 ICP-OES, AVIO 500).
[0171] <Measurement of Elemental Content and Atomic Ratio by X-ray Photoelectron Spectroscopy (XPS)> The elemental content (at%) and atomic ratio on the surface of the negative electrode active material were confirmed by XPS (Nexsa ESCA System, Thermo Fisher Scientific (ESCA-02)).
[0172] Specifically, for each sample, a survey scan spectrum and a narrow scan spectrum were obtained, and then a survey scan spectrum and a narrow scan spectrum were obtained while performing a depth profile. The depth profile was performed up to 3000 seconds using monatomic Ar ions. The measurement and data processing conditions are as follows.
[0173] - X-ray source: Monochromated Al K α (1486.6 eV) - X-ray spot size: 400 μm - Sputtering gun: Monatomic Ar (energy: 1000 eV, current: low, raster width: 2 mm) - Etching rate: 0.09 nm / s for Ta2O5 - Operation mode: CAE (Constant Analyzer Energy) mode - Survey scan: pass energy 200 eV, energy step 1 eV - Narrow scan: scanned mode, pass energy 50 eV, energy step 0.1 eV - Charge compensation: flood gun off - SF: Al THERMO1 - ECF: TPP-2M - BG subtraction: Shirley
[0174] Based on the total content of 100 at% of the elements measured on a 100 s basis under the above conditions, the content and atomic ratio of each element were calculated.
[0175] The compositions of the negative electrode active materials produced in the above examples and comparative examples are as shown in Table 1 below.
[0176] [Table 1]
[0177] <Experimental example: Discharge capacity, initial efficiency, life (capacity retention) characteristic evaluation> Anode manufacturing The negative electrode material used was a mixture of the composite negative electrode active material produced in Example 1 and graphite (average particle size (D50): 20 μm) as a carbon-based active material in a weight ratio of 20:80.
[0178] The negative electrode material, styrene-butadiene rubber (SBR) as a binder, Super C65 as a conductive material, and carboxymethyl cellulose (CMC) as a thickener were mixed in a weight ratio of 96:2:1:1, and the mixture was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry.
[0179] The negative electrode slurry was applied to one surface of a copper current collector (thickness: 15 μm) at 3.6 mAh / cm 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 50 μm), which was used as the negative electrode of Example 1 (thickness of negative electrode: 65 μm).
[0180] Moreover, negative electrodes of Examples 2 and 3 and Comparative Examples 1 to 3 were produced in the same manner as in Example 1, except that the negative electrode active material of Example 1 was replaced with the negative electrode active materials of Examples 2 and 3 and Comparative Examples 1 to 4, respectively.
[0181] Secondary battery manufacturing A lithium metal foil was prepared as the positive electrode.
[0182] A porous polyethylene separator was interposed between the negative and positive electrodes of Examples 1 to 3 and Comparative Examples 1 to 3 prepared as above, and an electrolyte was injected to prepare coin-shaped half cells of Examples 1 to 3 and Comparative Examples 1 to 3, respectively.
[0183] The electrolyte used was a solution in which ethyl methyl carbonate (EMC) and ethylene carbonate (EC) were mixed at a volume ratio of 7:3, in which 0.5% by weight of vinylene carbonate (VC) was dissolved, and LiPF6 was dissolved at a concentration of 1M.
[0184] Discharge capacity, initial efficiency, and life (capacity retention) characteristic evaluation The secondary batteries produced in Examples 1 to 3 and Comparative Examples 1 to 3 were evaluated for discharge capacity, initial efficiency, and cycle capacity retention rate using an electrochemical charger / discharger.
[0185] The cycle capacity retention was measured at 25°C, with the first and second cycles being charged and discharged at 0.1C, and from the third cycle onwards, the charge and discharge were performed at 0.5C (charge conditions: CC / CV, 5mV / 0.005 cut-off, discharge conditions: CC, 1.5V cut-off).
[0186] The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results after one charge / discharge.
[0187] The capacity retention was calculated as follows: Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at 1st cycle)} x 100 (In the above formula, N is an integer of 1 or more.)
[0188] The capacity retention (%) at the 50th cycle is shown in Table 2 below.
[0189] <Experimental example: Processability (amount of slurry gas generated) characteristic evaluation> As the negative electrode material, a mixture of the negative electrode active material produced in the above-mentioned Examples and Comparative Examples and graphite (average particle size (D50): 20 μm) as a carbon-based active material in a weight ratio of 15:85 was used.
[0190] As the negative electrode material, styrene-butadiene rubber (SBR) as the binder, Super C65 as the conductive material, and carboxymethyl cellulose (CMC) as the thickener were mixed at a weight ratio of 96:2:1:1, and this was added to distilled water as a solvent for forming the negative electrode slurry to prepare a negative electrode slurry.
[0191] Each of the negative electrode slurries was put into an aluminum pouch with a volume of 7 mL and sealed.
[0192] The difference between the weight of the aluminum pouch containing the negative electrode slurry in the air and the weight in water at 23°C was determined, and this was divided by the density of water at 23°C to measure the volume of the gas immediately after manufacturing the negative electrode slurry.
[0193] Next, after storing the aluminum pouch containing the negative electrode slurry at 60°C for 3 days, the difference between the weight of the aluminum pouch containing the negative electrode slurry in the air and the weight in water at 60°C was determined, and this was divided by the density of water at 60°C to measure the volume of the gas after storing the negative electrode slurry for 7 days.
[0194] The difference between the volume of the gas measured after storing the negative electrode slurry for 7 days and the volume of the gas measured immediately after manufacturing the negative electrode slurry was defined as the gas generation amount and is shown in Table 2 below.
[0195]
Table 2
[0196] The negative electrode active material according to the present invention is silicon-based particles containing SiO x (0 < x < 2) and Li compounds; a first carbon layer; a second carbon layer; LiF; and CF aThose including (0 < a < 4), Examples 1 to 3 using the negative electrode active material of the present invention were excellent in discharge capacity, initial efficiency, and capacity retention rate, and it was confirmed that there was no gas generation amount in the slurry or it was significantly low. This is because the negative electrode active material of the present invention is provided with two carbon layers, preventing lithium by-products from reacting with moisture, and CF a It is considered that (0 < a < 4) maximizes the hydrophobicity of the two carbon layers, effectively passivating the particles in the aqueous slurry.
[0197] On the other hand, in Comparative Example 1, the negative electrode active material contains only one carbon layer and does not contain LiF and CF a (0 < a < 4). It was confirmed that the moisture in the slurry easily reacts with the silicon-based particles and lithium by-products to generate gas, resulting in a decrease in discharge capacity, initial efficiency, and capacity retention rate.
[0198] In Comparative Example 2, the negative electrode active material contains two carbon layers but does not contain LiF and CF a (0 < a < 4). It was still confirmed that the reactivity between moisture and the silicon-based particles is large, resulting in a decrease in discharge capacity, initial efficiency, and capacity retention rate.
[0199] In Comparative Example 3, LiF was coated on the surface of the negative electrode active material. Although the silicon-based particles were passivated by LiF, the degree was low, and it was still confirmed that the gas generation amount was large and the discharge capacity, initial efficiency, and capacity retention rate were not improved.
[0200] Therefore, in the present invention, silicon-based particles, LiF, and CF a (0
Claims
1. SiO x (0<x<2) and a silicon-based particle comprising a Li compound; a first carbon layer provided on at least a portion of the surface of the silicon-based particle; a second carbon layer provided on at least a portion of a surface of the first carbon layer; LiF; and CF a (0<a<4); A negative electrode active material comprising:
2. The negative electrode active material according to claim 1 , which satisfies the following formula A: [0010] In the formula A, the element content is based on 100 at % of the sum of all elements measured in 100 seconds by surface analysis of the negative active material using X-ray photoelectron spectroscopy.
3. The negative electrode active material according to claim 1 , wherein an atomic ratio of C to Li (C / Li ratio) of the negative electrode active material is greater than 10 as determined by surface analysis of the negative electrode active material using X-ray photoelectron spectroscopy.
4. The LiF and the CF a The negative electrode active material according to claim 1 , wherein (0<a<4) is provided on the silicon-based particles.
5. The CF a The negative electrode active material according to claim 1 , wherein (0<a<4) is provided on a surface of the second carbon layer.
6. 2 . The negative electrode active material according to claim 1 , wherein the F content of the negative electrode active material is 10 at % or more and 50 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
7. 2 . The negative electrode active material according to claim 1 , wherein a Li content according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 0.1 at % or more and less than 10 at %.
8. 2. The negative electrode active material of claim 1, wherein the oxygen content of the negative electrode active material is 15 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
9. 2. The negative electrode active material of claim 1, wherein a Si content of the negative electrode active material is 7 at % or less according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy.
10. 2. The negative electrode active material according to claim 1, wherein a C content according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 50 at % or more.
11. 2 . The negative electrode active material according to claim 1 , wherein an atomic ratio of F to O (F / O ratio) according to a surface analysis of the negative electrode active material by X-ray photoelectron spectroscopy is 1 or more.
12. The CF a The negative electrode active material according to claim 1 , wherein the content of (0<a<4) is greater than the content of LiF.
13. SiF b The negative electrode active material according to claim 1 , further comprising: (0<b<4).
14. The negative electrode active material of claim 1, comprising 0.1 to 40 parts by weight of Li based on 100 parts by weight of the total negative electrode active material.
15. 2. The negative active material of claim 1, wherein a total content of the first carbon layer and the second carbon layer is in a range of 1 to 50 parts by weight based on 100 parts by weight of the total negative active material.
16. SiO x forming a silicon-based particle comprising a compound of (0<x<2) and Li, the particle having a first carbon layer on at least a portion of the surface thereof; forming a second carbon layer on at least a portion of the surface of the first carbon layer; and subjecting the silicon-based particles to a fluorine plasma treatment; The method for producing the negative electrode active material according to any one of claims 1 to 15, comprising:
17. The fluorine plasma treatment step includes: The silicon-based particles are placed in a plasma chamber and then CF 4 injecting gas; increasing the pressure within the plasma chamber; and forming a plasma in the plasma chamber; The method for producing a negative electrode active material according to claim 16 , comprising:
18. A negative electrode comprising the negative electrode active material according to any one of claims 1 to 15.
19. A secondary battery comprising the negative electrode according to claim 18.
Citation Information
Patent Citations
Silicon-based lithium storage material and preparation method thereof
CN112219295A
Manufacturing method of negative active material, negative active material thereof and lithium secondary battery comprising the same
KR1020130045212A